2009
DOI: 10.4049/jimmunol.0900819
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an N-Terminal Recognition Site in TLR9 That Contributes to CpG-DNA-Mediated Receptor Activation

Abstract: Although it is well established that TLR9 recognizes CpG-DNA, the structural details of ligand-receptor interaction are still mostly unknown. The extracellular domain of TLR9 is composed of 25 leucine-rich repeat (LRR) motifs, 5 of which bear inserting sequences that do not conform to the LRR consensus motif. In this study, we show that the functional integrity of the extracellular domain of murine TLR9 is lost by deletion of individual LRR motifs. When deleting only the inserting sequences, we observed that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 35 publications
4
107
5
Order By: Relevance
“…TLR9N þ C is primarily responsible for the DNAdependent TLR9 responses observed in DCs. A previous study using deletion mutations at TLR9N suggested that TLR9N is required for interaction with DNA and subsequent TLR9 activation 23 . In the present study, we employ another approach, a complementation strategy, and similarly conclude that TLR9N is required for TLR9 responses.…”
Section: Discussionmentioning
confidence: 99%
“…TLR9N þ C is primarily responsible for the DNAdependent TLR9 responses observed in DCs. A previous study using deletion mutations at TLR9N suggested that TLR9N is required for interaction with DNA and subsequent TLR9 activation 23 . In the present study, we employ another approach, a complementation strategy, and similarly conclude that TLR9N is required for TLR9 responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, this functional cleavage of TLR9 remains controversial based on the importance of the amino-terminal region of TLR9 for CpG DNA recognition and binding (Peter et al 2009). Interestingly, a study reported TLR9 to be expressed in the cell surface of murine splenic DCs using TLR9N-and TLR9C-specific antibodies and further explained that, succeeding the cleavage of TLR9 in the endolysosome, the amino-terminal cleaved fragment (TLR9N) remains associated with truncated TLR9 forming the complex TLR9þC, which acts as a bona fide DNA sensor; however, TLR9C alone could not recognize DNA (Onji et al 2013).…”
Section: Cd11bmentioning
confidence: 99%
“…In jawless vertebrates, combinatorial assembly of LRR gene segments in variable lymphocyte receptors generates the structural diversity for antigen recognition and forms the basis of an adaptive immune system (4,5). Toll-like receptors (TLRs) and NOD-like receptors (NLRs) recognize via the LRR domain, molecular determinants from a structurally diverse collection of bacterial, fungal, viral, and parasite-derived components (6,7). Mutations or polymorphisms in more than 30 LRR-containing proteins have been implicated in human diseases to date, notably polymorphisms in NOD2 in Crohn disease (8,9), CIITA in rheumatoid arthritis and multiple sclerosis (10), and TLR5 in Legionnaire disease (11).…”
mentioning
confidence: 99%